HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN TINDAKAN PERAWATAN KEHAMILAN PADA IBU HAMIL YANG MENGALAMI ABORTUS SPONTAN DI KLINIK BIDAN NERLI DESA SAMPE RAYA KECAMATAN BAHOROK KABUPATEN LANGKAT TAHUN 2013 - Nency Respina; Ria Masniari Lubis; Asfriyati ,MKes (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Abstract Abortion is one problem in reproduction in Indonesia even abortion is causal factor of bleeding and maternal mortality. The care of pregnant woman is one of sustainable program during pregnancy and partum that consist of education, screening, early detection, prevention, treatment, rehabilitation in order to provide the pregnant woman with safety and comfort that enable them to case their baby. This research aims to study a correlation of knowledge and attitude to the care treatment during pregnancy of the pregnant women who take spontaneous abortion in delivery clinic of Midwife Nerli in village of Sampe Raya sub disrict of Bahorok. District of Langkat in 2013. This research is analytic descriptive study by cross sectional design approach. The population is all of pregnant women who have spontaneous abortion at Delivery Clinic of Midwefe Nerli, up to May 2013 for 54 persons. The result of study indicates that good care treatment 40.7% and poor care treatment 59.3%. There is a significant correlation between knowledge (p = 0.016) and attitude (p = 0.024) to the care treatment of pregnancy to the pregnant women that have spontaneous abortion at delivery clinic midwife Nerli in village of Sampe Raya. It is suggested to the pregnant women to pay attention to her health and use the health service facilities by check up the pregnancy not less than 4 times and pay attention to the food consumption pattern to have a health fetus. Delivery Clinic of Midwife Nerli in village of Sampe Raya must increase health service specially in assessment of antenatal care and provide the pregnant women with information about the condition of the mother that cause the pregnancy complication. Keywords: Treatment, Knowledge, Attitude, Pregnancy Care, Abortion.